INNOVATIVE TRENDS IN VOCATIONAL TEACHER EDUCATION: A CAREER COUNSELOR FOR THE NEW UKRAINIAN SCHOOL - Liudmyla Khoruzha; Mariia Bratko; Liliya Hrynevych (Неперервна професійна освіта: теорія та практика)
The article considers the problem of training career counselors for the New Ukrainian School as a modern innovative trend. It is updated in the context of the introduction of three-year specialized education in Ukraine. A career counselor performs the function of a mediator between a person and his or her possible choice of profession, helps him or her identify and use his or her talents and abilities to achieve significant goals. A content analysis of scientific sources on the problem are carried out, which originates at the turn of the nineteenth and twentieth centuries. Modern foreign scientific researchers are highlighted, for example, the theory of vocational choice, as well as other theories of career development. The analysis and systematization of research on career development made it possible for scientists to systematize five groups of theories: substantive, procedural, substantive-procedural, constructivist, and broad explanation theories. It is considered the development of Ukrainian scientists on the issues of career guidance and career counseling: a scientific thesaurus on the problem is formulated, and relevant scientific research is carried out. However, theoretical generalizations have not been implemented in practice: Ukrainian higher education institutions do not provide comprehensive systematic professional training for career specialists. The authors of the article outline some prospects for the professional training of relevant specialists; define the range of potential job responsibilities of a career counselor; present a model framework of competencies of a career counselor working in a Ukrainian general secondary education institution; and present the content of innovative educational disciplines necessary for the professional and pedagogical training of future career counselors in the New Ukrainian School.